HEMODIALYSIS TUNNELED CATHETERS LOCK WITH TAUROLOCK™ VERSUS A COMBINATION OF GENTAMYCINE AND HEPARINE - Biser K. Borisov; Vanya T. Vasileva (Peytchinski Publishing, 2023)
Purpose: Catheter-related infections and thrombosis are the most common complications associated with the use of tunneled hemodialysis catheters. The aim of our study was to determine the incidence of these complications in patients who underwent "locking" of their tunneled catheters and compare the cost of different options with their effect. Materials and Methods: The study was conducted in the period 01.10.2021 - 31.03.2022. Twenty-three men and twenty-two women with a mean age of 60.82 (+/-13.629) years were randomly divided into three groups of 15 (fifteen) people each. Group A - catheter locking with TauroLock™ only, group B - with gentamicin and heparin; group C - with TauroLock™ for three months, then with heparin and gentamicin for the next three months. Results: The median duration for tunneled catheters was 8,105 catheter-days. One complication was reported in each of the three groups. Reported costs for patients treated with TauroLock™ were calculated at 3 EUR/each dialysis session and for patients treated with gentamicin and heparin - 0.88 EUR/dialysis session. Conclusion: The data from our study unequivocally support the thesis that locking the catheter with a TauroLock™ is comparable to the effect of the solution containing an antibiotic and anticoagulant.